The Success of the Implementation of the Independent Curriculum in Shaping the Pancasila Student Profile Character of Students at SMP Negeri 1 Rantau Selamat - Rosminawati Rosminawati; Yusaini Yusaini; Lathifah Hanum (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The Independent Curriculum at SMP Negeri 1 Rantau Selamat is implemented in stages. Based on the results of observations conducted at SMP Negeri 1 Rantau Selamat, during the learning process, teachers only focus more on student learning outcomes and less focus on character value formation. Problem formulation: 1). How is the implementation of the Independent Curriculum for students at SMP Negeri 1 Rantau Selamat?, 2). How is the character formation of the Pancasila Student Profile in students at SMP Negeri 1 Rantau Selamat?, 3). How is the success of the implementation of the Independent Curriculum towards the development of the Pancasila Student Profile character in students at SMP Negeri 1 Rantau Selamat?, the research method is carried out with qualitative research with data collection techniques carried out by observation, interviews and documentation. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. The research findings are as follows: 1) The implementation of the Independent Curriculum at SMP Negeri 1 Rantau Selamat was effective through project-based learning (P5) and differentiated learning strategies, which encouraged active student involvement in the learning process. 2) The character development of the Pancasila Student Profile in students is evident in the growth of independence, social awareness, creativity, discipline, and critical thinking skills, which are internalized in daily learning activities. 3) The successful implementation of the Independent Curriculum is reflected in positive changes in student attitudes and behavior, resulting in more self-confidence, responsibility, caring, and the ability to actualize Pancasila values in real lifeCharacter Development